Effectiveness of intravenous clarithromycin followed by oral clarithromycin in acute exacerbation of asthma with respiratory tract infection (Faculty of Medicine Universitas Indonesia, 2007)
In addition to its antimicrobial activity, macrolides have an immunomodulatory effect that may be beneficial to patients with asthma. This quasi-experimental study aimed to determine the effect of intravenous clarithromycin followed by oral administration in 37 patients with acute exacerbations asthma caused by respiratory tract infection during January - December 2005. Patients with mild to moderate exacerbations of asthma with respiratory tract infection meeting the inclusion and exclusion criteria were given intravenous clarithromycin 2 x 500 mg/day for not more than 5 days and followed by oral clarithromycin 2 x 500 mg/day for 7 days. Outcome variables were improvement of clinical symptoms according to the asthma exacerbation score and peak expiratory flow rate (PEFR). After 10 days, treatment resulted significant improvement in total asthma exacerbation score and morning PEFR in 35 patients enrolled this project. Based on clinical improvement and laboratory findings, the number of days required for intravenous clarithromycin was less then 3 days for 21 subjects, 3-5 days in 14 subjects. The most common causative pathogens were S. β-haemolyticus and Streptococcus sp. It was concluded that clarithromycin improved clinical symptoms and PEFR in exacerbation of asthma caused by respiratory tract infection. (Med J Indones 2007; 16:7-13) Keywords: Claritromycin, asthma exacerbation, respiratory tract infection